ANALISIS YURIDIS KASUS TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH ANAGGOTA TNI AKTIF YANG MENDUDUKI JABATAN SIPIL - Bunga Ali La Ode; Juhad Saputra Muh (Jurnal Ilmu Hukum Kanturuna Wolio, 2026)
This research aims to provide a juridical analysis of corruption crimes committed by active members of the Indonesian National Armed Forces (TNI) who hold civilian positions. The primary focus is on the conflict of authority between Military Courts and the Corruption Eradication Commission (KPK) in enforcing the law against military personnel involved in corruption. Using a normative-juridical and conceptual approach, and employing literature review as the data collection method, this study examines relevant legal frameworks including Law Number 31 of 1997 on Military Courts and Law Number 31 of 1999 jo. Law Number 20 of 2001 on the Eradication of Corruption Crimes. The findings indicate that although active TNI members are subject to Military Courts, in the context of corruption committed while holding civilian office, the general court system—particularly the KPK—has the authority to prosecute such cases, based on the legal principle of lex specialis derogat legi generali. This study recommends harmonization of overlapping regulations to prevent normative conflicts in the prosecution of corruption cases involving active military personnel.